(3GdCSGSjGJ hGdeSJMOKGJs - (3YHO GdeWdH(B, (3YHO GdMejOs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2009)
(3GdfbhO hGdHfhc hYdGbJgG HGdEbJUGO hGdfTGW GdEbJUGOj(B- (3GdJYQja HGdfbhO hJWhQgG hhXGFagG(B- (3CfhGY GdfbhO hEbJUGOjGJgG(B- (3GdJYQja HGdHfhc hCfhGYgG hhXGFagG(B- (3GdEFJeGf GdeUQaj hCgOGag hCfhGYg heNGWQg(B- (3EbJUGOjGJ GdHfhc GdJLGQjI(B- (3GdEOGQI GdeUQajI dehGQO hESJNOeGJ GdHfc GdJLGQj ddehGRfI(B- (3GdHfhc GdJLGQjI hNdb GdfbhO(B- (3GdSjGSI GdfbOjI(B- (3GdfXQjI GdcdGSjcjI hGdMOjKI hGdeYGUQI(B- (3GdJVNe CfhGYg, CSHGHg hBKGQg(B- (3GdfXGe GdfbOj GdOhdj hGdeDSSGJ GdfbOjI hGdeUQajI GdOhdjI(B- (3ebQQGJ heYGjjQ dLfI HGRd GdeUQajI dEOGQI GdeNGWQ hGdEUdGM GdeUQajs
(3GdeQGLY U(B.405s
Keywords: (3EbJUGOjGJ (B-(3GdfbhOs; (3GdSjGSI GdfbOjIs; (3GdfbhO hGdHfhcs